Method for preparing porous iron phosphate through emulsion reaction

The method of preparing porous iron phosphate through emulsification reaction solves the problems of complex methods, high cost and poor structural stability when preparing three-dimensional porous iron phosphate materials in the prior art, and realizes porous iron phosphate materials with high specific surface area and high porosity , improves the electrochemical properties of the material.

CN119430118APending Publication Date: 2025-02-14HUBEI XINGFA CHEM GRP CO LTD

Patent Information

Application Number
CN202411635879.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, when preparing three-dimensional porous structure iron phosphate materials, the method is complex, costly, and poor structural stability, making it difficult to achieve industrialization.

Method used

The method of preparing porous iron phosphate by emulsification reaction is adopted to achieve controllable structure of three-dimensional porous structures through emulsification foaming. The synthesis of iron phosphate retains the three-dimensional porous structure of the emulsified foam, simplifying the process and reducing costs.

Benefits of technology

Porous iron phosphate materials with high specific surface area and high porosity are achieved, which improves the structural stability and electrochemical performance of the material, and is suitable for the preparation of high-ratio lithium iron phosphate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430118A_ABST
    Figure CN119430118A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing porous iron phosphate through an emulsion reaction. The method comprises the following steps: (1) reacting an iron source and a phosphorus source according to a certain proportion to prepare an iron phosphate precursor; (2) reacting the iron phosphate precursor with a foaming agent to obtain emulsified iron phosphate dihydrate; (3) adding a cross-linking agent for further emulsification and dispersion, and adding a curing agent to obtain cured iron phosphate dihydrate; and (4) drying, calcining and crushing the iron phosphate dihydrate to obtain the porous iron phosphate. The method is specifically characterized in that the porous iron phosphate with the three-dimensional foam structure is finally obtained through the processes of emulsification foaming, curing reaction, calcination pore-forming and the like in sequence in the iron phosphate preparation process. The iron phosphate material prepared by the method has rich three-dimensional reticular porous structures, high specific surface area and high porosity. The lithium iron phosphate material prepared from the precursor material is high in electronic conductivity and can adapt to a high-rate lithium iron phosphate process. In addition, the raw materials used in the preparation process are cheap and easy to obtain, the preparation process is stable and controllable, and the iron phosphate prepared by the process has better application value and economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technical solution mainly relates to the technical fields of iron phosphate preparation, emulsifier foaming and porous material preparation, and specifically to a method for preparing porous iron phosphate by using an emulsification reaction. Background Art

[0002] Lithium iron phosphate batteries have gradually become the main electrode material for power and energy storage batteries due to their stable voltage platform, high battery specific capacity and low raw material cost advantages. As the core material of the entire lithium iron phosphate battery, the performance of lithium iron phosphate materials directly affects the energy density, cycle life and safety performance of the battery. Iron phosphate is the key raw material for the synthesis of lithium iron phosphate materials, and its structure and performance directly affect the physical and electrochemical properties of lithium iron phosphate materials. Related studies have shown that the rich three-dimensional porous structure of battery-grade iron phosphate is conducive to the insertion and extraction of lithium ions, which can effectively accelerate the diffusion rate of lithium ions, reduce the internal resistance of the material, and improve the electrochemical properties of lithium iron phosphate materials. Patent CN118183654A obtains a three-dimensional porous template by etching PMMA microspheres in the iron-based zeolite imidazole skeleton material template, and obtains a honeycomb porous structure iron phosphate material after subsequent treatment. This method improves the porosity of the material by constructing a three-dimensional porous structure on the one hand, and improves the electron mobility of the material by using the residual graphene quantum dots in the template to composite iron phosphate. However, there are still some problems in the preparation of iron phosphate by this method: first, the method is relatively complex and costly, making it difficult to industrialize; second, the structure of iron phosphate constructed by this method depends entirely on the iron-based imidazole skeleton template, and the structure is completely limited by the template material; finally, template etching faces the problem of uneven etching thickness and number of etched holes. The stability of the etching method directly affects the structural stability of the material and the product performance. Therefore, how to use a stable, simple, and efficient method to construct a rich three-dimensional porous structure and improve the structural stability of iron phosphate materials is an important challenge in the current preparation of three-dimensional porous iron phosphate materials and the improvement of the physical and electrochemical properties of lithium iron phosphate materials. Summary of the invention

[0003] In order to achieve the above-mentioned object, the present invention provides a method for preparing porous iron phosphate by emulsification reaction, which realizes the controllable construction of three-dimensional porous iron phosphate by emulsification foaming. The method synthesizes iron phosphate while retaining the three-dimensional porous structure of emulsified foam. The synthesis method is simple and efficient and can be industrially scaled up. The preparation method comprises the following steps: S1. Precursor reaction: mixing an iron source and a phosphorus source and adding an alkali solution to obtain an iron phosphate precursor; wherein the mass ratio of the iron source, the phosphorus source, and the alkali solution is 1:1.0-1.05:1.4-1.6; S2, emulsification reaction: filter and wash the precursor in S1 until the conductivity is 5-10 mS·cm -1A filter cake is obtained; the filter cake and dilute phosphoric acid are then added to a reactor in a ratio of 1:1.6-1.7, and dispersed evenly at 800-1000 rpm, and then a foaming agent is added to the reactor in a certain amount to obtain an emulsified slurry, and then aged at 90-100 ° C for 1-2 h to obtain an emulsified ferric phosphate dihydrate slurry; S3, curing reaction: add 5-10% of a crosslinking agent to the emulsified ferric phosphate dihydrate slurry obtained in S2, mix well, add 1-5‰ of a curing agent, let stand and cure for 20-30 min, then wash the slurry to obtain ferric phosphate dihydrate; S4, dehydration reaction: drying, crushing and calcining the dihydrate iron phosphate in S3 to obtain porous iron phosphate.

[0004] In step S1, the iron source is one or more of ferric sulfate, ferric chloride, and ferric nitrate; In step S1, the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, and sodium dihydrogen phosphate; The liquid alkali in step S1 is one or more of sodium hydroxide, ammonia water and potassium hydroxide.

[0005] In step S2, the foaming height is achieved by adjusting the foaming agent dripping rate and the stirring speed, and the foaming agent dripping rate satisfies the following formula: Where, O= , where A is the reaction coefficient, ω is the stirring speed, h is the liquid level, and O is the drop acceleration of the foaming agent feed.

[0006] The foaming agent is prepared by mixing sodium dodecyl sulfate, dodecanol and gum arabic in a ratio of 1:1-2:1-3; The mass ratio of the filter cake, phosphoric acid and foaming agent is 1:1.6-1.7 0.03-0.05; The stirring speed is 800-1000 rpm.

[0007] In the technical solution, the amount of filter cake, phosphoric acid and foaming agent is controlled by the dripping speed. At the same time, under the above-mentioned stirring speed adjustment, the uniform stirring and foaming effect of the materials are achieved, the foaming height of the reactor is controlled to be 40%-60% of the total height of the reactor, and the foam volume density is optimized and adjusted, so that the size distribution of emulsified ferric phosphate dihydrate is more uniform, and the porous ferric phosphate finally obtained has a higher porosity.

[0008] In step S3, the crosslinking agent is obtained by mixing sodium lignin sulfonate, liquid phenol, NaOH and formaldehyde solution in a ratio of 1:9-10:4-5:12-14; this step is the synthesis of lignin-based phenolic resin.

[0009] The curing agent in step S3 is one or more of commonly used curing agents such as diphenylmethane diisocyanate, hexamethylenetetramine and propylene carbonate; this step is a curing reaction of the lignin-based phenolic resin.

[0010] In step S4, the drying temperature is 80-100°C, the drying time is 4-8 h, the sintering temperature is 500-800°C, and the sintering time is 4-8 h.

[0011] The method for preparing porous iron phosphate by emulsification reaction has the following beneficial effects: (1) The present invention adds a foaming agent during the preparation of iron phosphate to perform emulsification and foaming to obtain an iron phosphate precursor with a three-dimensional foam structure, and then solidifies to obtain a porous iron phosphate material with a rich three-dimensional pore structure. The material synthesized by this method has a three-dimensional network structure and a high specific surface area (BET is 15~20 m 2 / g), relatively high porosity (0.7~0.8%).

[0012] (2) During the preparation process of iron phosphate, the height of emulsified foaming is controlled, and the foam volume density is optimized and adjusted, so that the size distribution of emulsified iron phosphate dihydrate is more uniform, and the porosity of the porous iron phosphate obtained is higher; (3) The synthetic raw materials are cheap and readily available, and the reaction process is stable and controllable. The lithium iron phosphate prepared using this iron phosphate material has a high electronic conductivity (0.0005-0.0008%) and can be used to prepare high-rate lithium iron phosphate (1C>155 mAh / g), which has good practical and economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 SEM images of the iron phosphate prepared in Example 1 (left) and Comparative Example 1 (right) of the present invention.

[0014] Figure 2 XRD patterns of the iron phosphate prepared in Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0015] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the exact ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in the present invention.

[0016] The method for preparing porous ferric phosphate by emulsification reaction provided by the present invention comprises the following steps: S1. Precursor reaction: an iron source, a phosphorus source and an alkali solution are mixed in a ratio of 1:1.0-1.05:1.4-1.6 and added into a reactor to obtain an iron phosphate precursor; S2, emulsification reaction: filter and wash the iron phosphate precursor in S1 until the conductivity is 5-10 mS·cm -1 ; Then, the filter cake and dilute phosphoric acid are added to the reactor in a ratio of 1:1.6-1.7, and dispersed evenly at 800-1000 rpm, and then the foaming agent is added dropwise to the reactor to obtain an emulsified slurry, and aged at 90-100 ° C for 1-2 h to obtain an emulsified ferric phosphate dihydrate slurry; S3, curing reaction: add 5-10% of a crosslinking agent to the emulsified ferric phosphate dihydrate slurry obtained in S2, mix well, add 1-5‰ of a curing agent, let stand and cure for 20-30 min, then wash the slurry to obtain ferric phosphate dihydrate; S4, dehydration reaction: drying, crushing and calcining the dihydrate iron phosphate in S3 to obtain porous iron phosphate; The method for preparing high-rate lithium iron phosphate provided by the present invention comprises the following steps: S5, mixing the iron phosphate obtained in steps S1 to S4 with a lithium source and a carbon source, and spray drying to obtain a lithium iron phosphate precursor; S6. The lithium iron phosphate precursor is sintered in an inert atmosphere to obtain high-rate lithium iron phosphate.

[0017] In order to better understand the present invention, the content of the present invention is further described below in conjunction with embodiments and related drawings, but the content of the present invention is not limited to the following embodiments.

[0018] Example 1 A1: 180 g of ferrous sulfate and 185 g of monoammonium phosphate were dissolved in 4000 g of deionized water, and then sodium hydroxide solution (260 g, mass fraction 40%) was added dropwise into the reactor to obtain an iron phosphate precursor; A2: Filter and wash the iron phosphate precursor obtained in A1 until the conductivity is 5 mS·cm -1 A filter cake was obtained, and then 2000 g of the filter cake and 3200 g of dilute phosphoric acid were added to a reactor and dispersed evenly at 800 rpm. Then, 2 g of sodium dodecyl sulfate, 3 g of dodecyl alcohol and 4 g of gum arabic were mixed as a foaming agent and slowly added dropwise to the reactor, and then reacted at 90°C for 2 h to obtain an emulsified ferric phosphate dihydrate slurry; The rate of addition of the foaming agent satisfies O= , where A is 0.866, ω is the stirring speed of 800 rpm, h is the liquid level height of 6.5, and O is the dropwise acceleration of the foaming agent feed.

[0019] A3: Add 7 g of sodium lignin sulfonate, 65 g of liquid phenol, 30 g of NaOH and 85 g of formaldehyde solution to the emulsified ferric phosphate dihydrate slurry obtained in A2, stir for 30 min, add 5 g of diphenylmethane diisocyanate, let stand for 30 min, filter and wash to obtain a ferric phosphate dihydrate filter cake; A4: The dihydrate iron phosphate in A3 was dried at 100 °C for 8 h, crushed and calcined at 650 °C for 4 h to obtain porous iron phosphate; A5: lithium carbonate, graphite black and glucose are added to the iron phosphate prepared in step A4, wherein the molar ratio of FePO4:Li2CO3 is 1:0.6, and graphite black and glucose are added at 5% and 10% of the mass of the iron phosphate, respectively; deionized water is used as a dispersion medium, stirred for 1 hour, and then spray-dried to obtain a lithium iron phosphate precursor; A5: The lithium iron phosphate precursor is calcined at 800° C. for 12 h in a nitrogen atmosphere, and then naturally cooled to room temperature to obtain lithium iron phosphate.

[0020] like Figure 1 As shown in (a), the iron phosphate particles in Example 1 are relatively small (30-50 nm), the secondary particle agglomerates are three-dimensional network structures, the particles are staggered and distributed, and have a high space utilization rate. The product has a high porosity (0.7-0.8 m 3 / g).

[0021] Example 2-3 Example 2-3 is an example of changing the controller program in step A2, and the other conditions are consistent with Example 1. In Example 2, the opening O of the feed silo feed valve satisfies O= , wherein A is 0.866, the stirring paddle speed ω is 150 rpm, and the liquid level is 6.5; under the same conditions (same as Example 1), an emulsified ferric phosphate dihydrate slurry is obtained by reaction, and anhydrous ferric phosphate is obtained through subsequent steps.

[0022] In Example 3, the opening O of the feeding valve of the feeding bin satisfies O= , wherein A is 0.866, stirring speed ω=1000 rpm, and liquid level h is 10. Under the same conditions (same as Example 1), an emulsified ferric phosphate dihydrate slurry is obtained by reaction, and anhydrous ferric phosphate is obtained through subsequent steps.

[0023] Embodiment 4-6 Examples 4-6 are examples in which the ratio of the foaming agent in step A2 is changed, and the other conditions are the same as those in Example 1. In Example 4, 3 g of dodecanol and 4 g of gum arabic are used; under the same conditions (same as in Example 1), a reaction liquid slurry is obtained, and anhydrous iron phosphate is obtained through subsequent steps.

[0024] In Example 5, 2 g of sodium dodecyl sulfate and 4 g of gum arabic were used; the reaction was carried out under the same conditions (as in Example 1) to obtain a reaction liquid slurry, and anhydrous iron phosphate was obtained through subsequent steps.

[0025] Example 6 uses 2 g of sodium dodecyl sulfate, 4 g of dodecanol and 6 g of gum arabic; the reaction is carried out under the same conditions (same as Example 1) to obtain a reaction liquid slurry, and anhydrous iron phosphate is obtained through subsequent steps.

[0026] Examples 7-10 Examples 7-10 are examples in which the type of crosslinking agent in step A3 is changed, and the other conditions are the same as those in Example 1. In Example 7, 65 g of liquid phenol, 30 g of NaOH and 85 g of formaldehyde solution are used; under the same conditions (same as in Example 1), a reaction liquid slurry is obtained, and anhydrous iron phosphate is obtained through subsequent steps.

[0027] In Example 8, 7 g of sodium lignin sulfonate, 30 g of NaOH and 85 g of formaldehyde solution were used; the reaction was carried out under the same conditions (same as in Example 1) to obtain a reaction liquid slurry, and anhydrous iron phosphate was obtained through subsequent steps.

[0028] In Example 9, 7 g of sodium lignin sulfonate, 65 g of liquid phenol and 85 g of formaldehyde solution were used; the reaction was carried out under the same conditions (same as in Example 1) to obtain a reaction liquid slurry, and anhydrous iron phosphate was obtained through subsequent steps.

[0029] In Example 10, 7 g of sodium lignin sulfonate, 63 g of liquid phenol, 28 g of NaOH and 84 g of formaldehyde solution were used. Under the same conditions (same as in Example 1), a reaction liquid slurry was obtained, and anhydrous iron phosphate was obtained through subsequent steps.

[0030] Examples 11-12 Examples 11-12 are examples in which the type of curing agent in step A3 is changed, and the other conditions are the same as those in Example 1. In Example 11, 5 g of ethyl acetate (without curing activity) is added; the reaction is carried out under the same conditions (same as in Example 1) to obtain a reaction liquid slurry, and anhydrous iron phosphate is obtained through subsequent steps.

[0031] In Example 12, 5 g of propylene carbonate was added; the reaction was carried out under the same conditions (as in Example 1) to obtain a reaction liquid slurry, and anhydrous ferric phosphate was obtained through subsequent steps.

[0032]

[0033] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.

Claims

1. A method for preparing porous iron phosphate by emulsification reaction, characterized in that: The steps include: S1. Precursor reaction: mixing an iron source and a phosphorus source in a certain proportion and then adding an alkali solution to obtain an iron phosphate precursor; S2, emulsification reaction: filtering and washing the iron phosphate precursor in S1 to obtain a filter cake, then mixing the filter cake, phosphoric acid and a foaming agent to perform an emulsification reaction, and then reacting and aging under high temperature conditions to obtain an emulsified iron phosphate dihydrate slurry; S3, curing reaction: adding a crosslinking agent to the emulsified ferric phosphate dihydrate slurry in S2, adding a curing agent after emulsification and stirring, standing and curing for 10-15 minutes, and then washing the slurry to obtain ferric phosphate dihydrate; S4, dehydration reaction: drying, calcining and pulverizing the dihydrate iron phosphate in S3 to obtain porous iron phosphate.

2. The method for preparing porous iron phosphate by emulsification reaction according to claim 1, characterized in that: In step S1, the iron source is one or more of ferric sulfate, ferric chloride, and ferric nitrate; The phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, and sodium dihydrogen phosphate; The alkali solution is one or more of sodium hydroxide, ammonia water and potassium hydroxide.

3. The method for preparing porous iron phosphate by emulsification reaction according to claim 1, characterized in that: In step S1, the iron source and the phosphorus source are mixed in a ratio of 1:1.0-1.05, the stirring speed is 300-500 rpm, and the amount of alkali solution added is 1.4-1.6 of the mass of the iron source.

4. The method for preparing porous iron phosphate by emulsification reaction according to claim 1, characterized in that: In step S2, the foaming height is achieved by adjusting the foaming agent dripping rate and the stirring speed, and the foaming agent dripping rate satisfies the following formula: Where, O= , where A is the reaction coefficient, ω is the stirring speed, h is the liquid level, and O is the foaming agent feed rate.

5. The method for preparing porous iron phosphate by emulsification reaction according to claim 1, characterized in that: In step S2, pure water is used for washing until the conductivity is 5-10 mS·cm -1 ; The foaming agent is prepared by mixing sodium dodecyl sulfate, dodecanol and gum arabic in a ratio of 1:1-2:1-3; The mass ratio of the filter cake, phosphoric acid and foaming agent is 1:1.6-1.7:0.03-0.05; The stirring speed is 800-1000 rpm, and the aging temperature is 90-100 °C.

6. The method for preparing porous iron phosphate by emulsification reaction according to claim 1, characterized in that: In step S3, the cross-linking agent is obtained by mixing sodium lignin sulfonate, liquid phenol, NaOH and formaldehyde solution in a ratio of 1:9-10:4-5:12-14, and the amount of the cross-linking agent added is 5-10% of the total weight of the emulsified ferric phosphate dihydrate slurry.

7. The method for preparing porous iron phosphate by emulsification reaction according to claim 1, characterized in that: In step S3, the curing agent is one or more of diphenylmethane diisocyanate, hexamethylenetetramine and propylene carbonate, and the amount of the curing agent added is 1-5‰ of the total weight of the emulsified ferric phosphate dihydrate slurry.

8. The method for preparing porous iron phosphate by emulsification reaction according to claim 1, characterized in that: In step S4, the drying temperature is 80-100°C, the drying time is 4-8 h, the sintering temperature is 500-800°C, and the sintering time is 4-8 h.

9. The porous iron phosphate obtained by the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The porous iron phosphate is prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Honeycomb porous structure iron phosphate material as well as preparation method and application thereof

    CN118183654A

Cited By

  • Lithium manganese iron phosphate positive electrode material and preparation method thereof

    CN120717438A

  • Preparation method of ferrophosphorus with high specific surface area, high performance and low impurity

    CN120793871A

  • A method for preparing high specific surface area, high performance and low impurity ferrophosphorus

    CN120793871B